PENDIDIKAN SAINS DALAM AL-QUR’AN - Arini Siregar; Siti Nur Haliza; Asnil Aidah Ritonga; Ahmad Darlis (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
Science education basically places more emphasis on curiosity and then creates a passion for action so as to gain a deeper understanding of the nature of nature. From science education a person can develop his abilities, think inductively and deductively, can solve problems related to the natural surroundings both qualitatively and quantitatively. This research is included in library research (library) which makes the Al-Qur'an as the main data and uses interpretations written by mufassir and educational books related to journal content as secondary data. This study also uses thematic interpretation (maudu'i) as its approach. Verses related to science in the Qur'an can be found in surah Al-Mukminun verse 14 and Az-Zumar verse 6.